2018
DOI: 10.3389/fphar.2018.01374
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Curcumin Against Chemotherapy-Induced Side-Effects

Abstract: Cancer is still a severe threat to the health of people worldwide. Chemotherapy is one of main therapeutic approaches to combat cancer. However, chemotherapy only has a limited success with severe side effects, especially causing damage to normal tissues such as bone marrow, gastrointestine, heart, liver, renal, neuron, and auditory tissues, etc. The side-effects limit clinical outcome of chemotherapy and lower patients’ quality of life, and even make many patients discontinue the chemotherapy. Thus, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 74 publications
2
60
0
2
Order By: Relevance
“…These projects are at different stages (Phase I through Phase III) of execution. Curcumin also shows profound antitoxic properties in diverse target organs, such as, alleviation of neurotoxicity, cardiotoxicity, nephrotoxicity, hemato-toxicity, genotoxicity and hepatotoxicity [13,55]. Additional attributes that curcumin offers are its capacity to confer properties of electron receptors which destabilize reactive oxygen species (ROS), therefore explaining its antioxidant and anti-cell death (necrotic, apoptotic or aponecrotic) effects.…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These projects are at different stages (Phase I through Phase III) of execution. Curcumin also shows profound antitoxic properties in diverse target organs, such as, alleviation of neurotoxicity, cardiotoxicity, nephrotoxicity, hemato-toxicity, genotoxicity and hepatotoxicity [13,55]. Additional attributes that curcumin offers are its capacity to confer properties of electron receptors which destabilize reactive oxygen species (ROS), therefore explaining its antioxidant and anti-cell death (necrotic, apoptotic or aponecrotic) effects.…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
“…In this regard, curcumin-mediated enhanced expression of pro-apoptotic molecules such as BAK and BID, and reduced expression of anti-apoptotic molecules such as BCL-2, BCL-XL and MCL-1 in the chemotherapy-treated cancer cells remains an active area of research. Furthermore, curcumin's synergistic effect on docetaxel to activate tumor suppressor p53 and inhibit phosphoinositide 3-kinase (PI3K)/AKT, epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor type 2 (HER2) are noteworthy reports [53,55,57].…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
“…40 It has also been shown to reduce chemotherapy-induced toxic side effects. 41,42 To the best of our knowledge, curcumin has never been administered directly into the pleural cavity of animals, or humans. Therefore, the safety and compartmental distribution of intrapleural liposomal curcumin following intrapleural needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current studies have shown that curcumin is capable to hinder carcinogenesis in sensitive cells after chemotherapy and protects normal cells from the damages caused by chemotherapy [12,13]. According to antioxidative and anti-inflammatory properties of curcumin, a protective effect against kidney damages and renal toxicity following chemotherapeutic drugs administration has been reported [15,16]. Furthermore, it has been revealed that curcumin is able to show protecting effects against ischemic renal impairment by upregulation of antioxidant gene expression, mainly Mn-superoxide dismutase, the antioxidant enzyme in the mitochondrial matrix [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…According to antioxidative and anti-inflammatory properties of curcumin, a protective effect against kidney damages and renal toxicity following chemotherapeutic drugs administration has been reported [15,16]. Furthermore, it has been revealed that curcumin is able to show protecting effects against ischemic renal impairment by upregulation of antioxidant gene expression, mainly Mn-superoxide dismutase, the antioxidant enzyme in the mitochondrial matrix [15,16]. For the reason that many people are suffering worldwide from side effects of chemotherapy drugs, the aim of this study was to estimate the effects of curcumin in an experimental model of busulfan-induced renal toxicity with emphasis on importance of histological alterations.…”
Section: Introductionmentioning
confidence: 99%